Perspektif Teoritik Kekerasan dan Ancaman Kegagalan Pembangunan - Sukardi, Sukardi (Jurnal Ilmiah Administrasi Publik, 2015)
Development violence has become characteristics of three government regims of Indonesia in the last three decades. Yet, the characteristics of violence still become the main ways for government to solve public issues.Â  These characteristics of violence leads to violence action in the community. Through cultural perspective, this paper elaborates why and how systematic development violence was adopted become and the development policy implication to solve it.